Characterisation of presentations to a community‐based specialist addiction neuropsychology service: Cognitive profiles, diagnoses and comorbidities. (12th August 2020) - Gooden, James R.; Cox, Catherine A.; Petersen, Vanessa; Curtis, Ashlee; Manning, Victoria; Lubman, Dan I.
Abstract: Introduction and Aims: Cognitive impairment is a common feature of individuals with substance‐use disorders. However, research tends to exclude highly complex clinical cases, limiting the generalisability of findings for 'real‐world' populations. The objective of this study was to examine the complexities associated with addiction, substance use and cognitive impairment through the characterisation of client presentations to a newly established specialised addiction neuropsychology service. Design and Methods: Retrospective case file audit. Neuropsychological assessment reports for consenting clients over a 4‐year period were de‐identified and reviewed. Cognitive domains assessed included attention, processing speed, working memory, intellectual functioning, memory and executive functioning. Results: Of the 200 case files examined, the majority were male clients, with 11 years or lower of education and a history of daily substance use, with 30% continuing to use daily. Seventy‐one percent had a formal mental health diagnosis and 41% had reported a history of trauma. The most prevalent cognitive impairments were observed in complex attention (50%) and memory (40%). New diagnoses were conveyed in 25% of cases, comprising acquired brain injury (16%) and neurodevelopmental disabilities (9%). Discussion and Conclusions: It is common for clients with substance use histories referred to an addiction neuropsychology service to present with complex histories including psychosocial difficulties, comorbid mental health and medical issues and cognitive impairment. As such, careful diagnostic formulations are required when multiple factors may contribute to cognitive deficits. This study highlights the importance of a state‐wide specialist addiction neuropsychology service in supporting diagnostic clarification and informing relevant treatment approaches.